Geomorfološke vsebine in njihova zastopanost v razlagi pokrajinskih značilnosti Triglavskega narodnega parka v primerjalni luči - Kunaver, Jurij (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The article deals with the problem of appropriate role of relief and geomorphology in nature interpretation in the area and on the nature trails in the Triglav National Park. The six most famous nature trails and areas of interest do not prove a high enough quality in this respect. The worst example is the situation in the famous Valley of Seven Triglav Lakes. Some excellent examples of geomorphological nature trails in Alps, not far from Slovenia, show that, in this respect, a lot of work is still waiting for us.
Keywords: naravni parki; Triglav National Park; Triglavski narodni park; geomorfologija; geomorphology; topography; relief; education; izobraževanje; Slovenia; Slovenija